Desenvolvimento e caracterização de filmes biopoliméricos contendo vidro bioativo - Lemos, Ana Gabrielli (Universidade Federal de São Carlos, 2023)
Dental caries and periodontal disease are considered the most frequent global problems that affect human oral health. However, in cases of periodontitis, the exacerbated immune and inflammatory response of the organism itself is largely responsible for the destruction of the periodontal ligament and supporting bone. Thus, the therapeutic approach regarding the minimization of tissue damage, as well as their recovery, can be considered as relevant as combating the disease-causing microorganisms. A promising material for this application is bioactive glass (bioactive glass), which has been shown to be an excellent osteoinducer and efficient in inhibiting some microorganisms. In order to restore periodontal tissues, the present work developed a film-forming delivery system containing bioactive glass and allowing its prolonged release. Zein, a hydrophobic protein obtained from corn, was selected as the main material for film formation. When bioactive glass meets biological fluids, it forms a layer similar to hydroxyapatite, which is responsible for binding to bone. It also has osteoinductive capacity, soft tissue binding and antibacterial activity due to the high pH resulting from ion release. The results indicate that the obtained matrix is stable, and the precursors presented synergy in the film formation. With the incorporation of bioactive glass, the material became even more homogeneous and with more regular morphology. The release assays indicated that bioactive glass exhibited ion release activity and was therefore released in the simulated biological fluid.
Development and Characterization of Biopolymeric Films Containing Bioactive Glass
Keywords: Periodontite; Zeína; Biovidro; Zein; Periodontitis; Bioglass; CIENCIAS EXATAS E DA TERRA::QUIMICA